Changing Paradigm of Purchase Retention With Respect to Brand Love and Brand Engagement - Prakash, Ved (Journal of Finance, Business and Management Studies, 2024)
Businesses interact with their customers in an effort to maintain or improve their total brand equity. This study explores the relationship between brand engagement and brand love, as well as how these two factors interact to affect overall brand equity and purchase intent. Data gathered from 311 respondents using a self-administered survey were subjected to a two-stage analysis. The measurement model’s validity and reliability were examined in the first stage, and the structural model’s strength of the relationships was determined in the second. The study makes it possible to comprehend the causes of brand equity in great detail. It offers useful theoretical insights into the factors that affect how brand equity is formed. It also examines the impact of sociodemographic factors like gender and usage. Relationships are mediated by brand love and overall brand equity. By combining previously researched characteristics such as brand love, brand experience, total brand equity, and purchase intention into one comprehensive model, this study suggests a new branding framework. This study supports the notion that brand love and brand engagement are second-order constructs and crucial components of the brand mix. Relationships between a brand and its fans are controlled by usage and gender.